Epoxy/graphene nanocomposites – processing and properties: a review. Issue 90 (2nd October 2015) - Wei, Jiacheng; Vo, Thuc; Inam, Fawad
<x xml:space="preserve">Abstract</x> Graphene, a 2D fullerene, is a unique material because of its exceptional set of properties. This review has been focused on the processing methods and mechanical, electrical, thermal, and fire retardant properties of epoxy/graphene nanocomposites.